Investigating the influence of yarn characteristics on microfibre release from knitted fabrics during laundering - Hazlehurst, Alice; Sumner, Mark; Taylor, Mark (Frontiers in Environmental Science, 2024)
Microfibres generated and released during the use and laundering of textiles have been identified as an important source of environmental pollution. The quantity of microfibres released from a fabric can be influenced by several external factors, such as laundering conditions and consumer use, as well as intrinsic factors such as the fibre composition, yarn characteristics, and fabric structure. This study investigates the influence of various yarn characteristics on microfibre release from knitted fabrics as well as exploring the generation of microfibres during the knitting process. Fibre composition and the yarn spinning system has the greatest influence on microfibre release. The greatest quantity of microfibre was released from ring-spun lyocell (1313 ± 140 mg/kg) and the lowest quantity was released from vortex-spun polyester (80 ± 26 mg/kg). The yarn spinning system was also found to have a significant influence, with vortex-spun yarns consistently demonstrating lower microfibre release than corresponding ring-spun yarns, likely due to the reduced hairiness of yarns spun by the vortex system. The importance of fibre damage during the knitting process was also investigated. Several yarns demonstrated significantly greater microfibre release in knitted form compared to loose, hank form, but the scale of difference was found to be dependent on fibre composition.